2022
DOI: 10.3390/nu14122511
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of Dietary Fiber with Different Physicochemical Properties during Late Pregnancy Alters the Gut Microbiota and Relieves Constipation in Sow Model

Abstract: Constipation is a common problem in sows and women during late pregnancy. Dietary fiber has potential in the regulation of intestinal microbiota, thereby promoting intestinal motility and reducing constipation. However, the effects of fibers with different physicochemical properties on intestinal microbe and constipation during late pregnancy have not been fully explored. In this study, a total of 80 sows were randomly allocated to control and one of three dietary fiber treatments from day 85 of gestation to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 66 publications
1
22
0
Order By: Relevance
“…The dominant genera in the inoculum were norank_f_Prolixibacteraceae , DMER64 , norank_f_Bacteroidetes_vadinHA17 , Turicibacter , unclassified_f_Peptostreptococcaceae , Smithella , norank_f_Anaerolineaceae , Thermovirga , Clostridium_sensu_stricto_1 , and norank_f_Synergistaceae . These microorganisms are reported to be involved in hydrolysis, acidogenesis and acetogenesis to produce VFAs, which provide nutrients to methanogenic bacteria 37‐43 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dominant genera in the inoculum were norank_f_Prolixibacteraceae , DMER64 , norank_f_Bacteroidetes_vadinHA17 , Turicibacter , unclassified_f_Peptostreptococcaceae , Smithella , norank_f_Anaerolineaceae , Thermovirga , Clostridium_sensu_stricto_1 , and norank_f_Synergistaceae . These microorganisms are reported to be involved in hydrolysis, acidogenesis and acetogenesis to produce VFAs, which provide nutrients to methanogenic bacteria 37‐43 …”
Section: Resultsmentioning
confidence: 99%
“…These microorganisms are reported to be involved in hydrolysis, acidogenesis and acetogenesis to produce VFAs, which provide nutrients to methanogenic bacteria. [37][38][39][40][41][42][43] In R0, the Bifidobacterium (48.09%), Lactobacillus (26.04%), Prevotella (13.66%), Clostridium_sensu_stricto_12 (6.19%), and Olsenella (5.14%) genera were the dominant microorganisms in the final start-up period. Lactic bacteria such as Bifidobacterium and Lactobacillus accounted for lactic acid production, while the other prevalent bacteria were associated with VFA production.…”
Section: Microbial Community Analysis Of Semi-continuous Fermentationmentioning
confidence: 99%
“…A study compared the application effects of lignocellulose, resistant starch, and konjac flour on sows in late pregnancy. The highest scores of defecation frequency and stool consistency were found in sows of the resistant starch group ( Lu et al, 2022 ). The above results indicated that both fiber adsorption capacity and regulation of intestinal microbiota might affect fecal pH values.…”
Section: Discussionmentioning
confidence: 99%
“…High-amylose corn starch (RS2) increased the abundance of Bacteroides and the circulating levels of conjugated, primary, and secondary bile acids in obese mice, and higher levels of circulating bile acids have been related to improved energy homeostasis [19]. Resistant starch was found to increase the relative abundance of Turicibacter and strengthened gut barrier and facilitated 5-HT release from gut cells [31]. Resistant starch might also reduce the risk of dietary protein-induced colonocyte DNA damage via the regulation of fecal concentrations of the protein metabolite p-cresol; the fecal abundance of a p-cresol-producing bacterium, Clostridium from the Peptostreptococcaceae family, was reduced by resistant starch from high-amylose wheat [30].…”
Section: Gut Microbiota and Microbial Metabolites As The Target Of Re...mentioning
confidence: 99%